2023
DOI: 10.1177/17479541231153273
|View full text |Cite
|
Sign up to set email alerts
|

Considering perceptual experiences and adaptive actions in performance analysis of elite Formula Kite riders by combining qualitative data and measured key indicators of performance

Abstract: Formula Kite is a high-speed sailing sport using hydrofoils, recently included in the Olympic sports list. In Formula Kite, the riders’ technical abilities to reach and maintain high speed are key to achieving performance. The aim of the present study was to analyze Formula Kite riders’ performance during speed tests in practice sessions by combining qualitative descriptions of their lived perceptual experiences “from the inside” with measured correlates of performance. The courses of experience of four expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Furthermore, the studies of Terrien et al (2020Terrien et al ( , 2022Terrien et al ( , 2023aTerrien et al ( , 2023b in sailing have shown that the behavior of sports equipment affects the interplay between athletes and their equipment. Indeed, some sports equipment exhibits behaviors that are not directly controlled by the athletes.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the studies of Terrien et al (2020Terrien et al ( , 2022Terrien et al ( , 2023aTerrien et al ( , 2023b in sailing have shown that the behavior of sports equipment affects the interplay between athletes and their equipment. Indeed, some sports equipment exhibits behaviors that are not directly controlled by the athletes.…”
mentioning
confidence: 99%
“…This contrasts with the movements of a backpack, which stop if the runner stops moving, or the movement of a golf club, which directly depends on the forces applied by the golfer. The studies of Terrien et al (2020Terrien et al ( , 20222023a, 2023b were conducted within the course-of-experience framework (Poizat et al, 2022;Terrien et al, 2023;Theureau, 2006) with elite sailors. The aim of this research was primarily to study the interplay between humans, sports equipment, and the environment by analyzing sailors' intentions, expectations, knowledge, perceptions, and actions, in relation to the equipment's movements.…”
mentioning
confidence: 99%
See 3 more Smart Citations